Total intravenous anesthesia with propofol and dexmedetomidine in bitches submitted to ovary-hysterectomy (Research, Society and Development, 2022)
Total intravenous anesthesia is widely used in dogs, and the addition of adjuvants aims to complement analgesia and reduce the doses of propofol used. This study aimed to evaluate the association of dexmedetomidine and propofol in total intravenous anesthesia in dogs. Fifteen adults, healthy bitches weighing 13.8 ±4.7 kg were selected. After premedication with acepromazine and methadone. They were allocated to two groups: GDEX (n = 8) were administered dexmedetomidine (2 µg/kg bolus + 1 µg/kg/h IV) or control GC (n = 7) with saline, and then administered propofol to both groups. The animals were maintained on propofol, adjusted to the anesthetic plane, and supplemented with 100% oxygen. The following were evaluated: induction scale, electrocardiogram, heart and respiratory rates, systolic blood pressure with Doppler, end-tidal carbon dioxide pressure, and peripheral oxygen saturation. When necessary, fentanyl (2.5 µg/kg IV) was administered. In the end, propofol rate, fentanyl consumption, surgical time, extubation, anesthetic discharge, and bleeding score were recorded. There was a mean reduction of 46% in heart rate after administration of dexmedetomidine. At the same time after induction, the systolic blood pressure was 125 ±26 mmHg in the CG compared to 148 ±42 mmHg in the GDEX. There was also a reduction of 73% in the consumption of fentanyl and 29% in the rate of propofol. Also, the visual bleeding score was higher in the GDEX. In conclusion, the association of dexmedetomidine to the protocol decreased the rate of propofol and improved the intraoperative analgesia of bitches undergoing castration.